PENERIMAAN BERITA HOAKS MELALUI MEDIA SOSIAL SEBAGAI LITERASI INFORMASI DIKALANGAN REMAJA DI KOTA BANDA ACEH - Furqan Furqan; Muhammad Syarif; Syukur Kholil (Jurnal Dedikasi Pendidikan, 2023)
Based on observations, almost the average student uses a cell phone so that teenagers make social media a trend among these teenagers. Most of them know social media through other peers who attend other schools. The purpose of this research is to encourage youth literacy in the city of Banda Aceh in responding to information on social media, using social media to view information, and teenagers in the city of Banda Aceh in understanding the spread of hoax information on social media. The theory used in this study is the theory of media literacy. This research method uses a qualitative descriptive approach. Research informants consisted of Community Leaders, Academics, Students. Data collection techniques were carried out through observation, interviews and documentation. Based on the research results, it is known that teenagers literacy in the city of Banda Aceh in responding to information on social media can be grouped into two responses. First, students who respond well to news information by observing and understanding and looking for the truth so that they are not mistaken in conveying greetings to other parties. Second, there are students who have unfavorable responses, because they do not pay close attention and understand well, so that they convey news that sometimes is not true to other parties. The understanding of most adolescents in Banda Aceh City regarding the dissemination of information on social media is good, marked by a critical attitude towards understanding it, such as seeking the truth of the same information in other media, so that they are not mistaken in understanding information on social media. However, some students are also not careful in understanding information messages on Social Media, because they are considered to have no benefits for their lives. The understanding of adolescents in Banda Aceh City in spreading hoax information on social media is always careful and not easily provoked by news circulating